Criminal Law Reform: Restorative Justice and Child Protection in the 2023 Criminal Code (KUHP) - Oci Senjaya; Indra Yudha Koswara (Faculty of Law, Universitas Lampung, 2025)
This study examines criminal law reform in relation to the application of restorative justice and child protection under the 2023 Criminal Code (KUHP). It addresses two research questions: (1) how the principle of restorative justice is applied in the 2023 KUHP in cases involving children, and (2) the extent to which the 2023 KUHP guarantees legal protection for children as victims and perpetrators of criminal acts. The research uses a normative doctrinal method with a literature study approach to relevant legislation and legal doctrines. The study identifies a gap in the implementation of restorative justice, which has not yet fully accommodated the need for comprehensive child protection. The findings indicate that the 2023 Criminal Code represents significant progress in integrating restorative justice as an alternative mechanism for resolving criminal cases; however, legal protection for children still requires stronger implementation mechanisms to align with the principles of children’s rights and the special protection mandated by national and international law.